Process and impact of dialectical behaviour therapy: a systematic review of perceptions of clients with a diagnosis of borderline personality disorder - Little, Hannah; Tickle, Anna; das Nair, Roshan (Wiley, 2017)
Purpose: To identify, appraise and synthesise findings from qualitative studies of individuals diagnosed with Borderline Personality Disorder who have experienced Dialectical Behaviour Therapy, to gain further understanding of their perceptions of the process and impact of therapy.